2015
DOI: 10.7150/ijbs.11907
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Induces Changes in Immunity in Trichinella spiralis-Infected Rats

Abstract: Sleep is considered an important predictor of immunity. A lack of sleep may reduce immunity, which increases susceptibility to any type of infection. Moreover, sleep deprivation in humans produces changes in both, the percent of circulating immune cells (T cells and NK cells) and cytokine levels (IL-1, IFNγ, TNΦ-αα, IL-6 and IL-17). The aim of our study was to investigate whether sleep deprivation produces deregulation on immune variables during the immune response generated against the helminth parasite Trich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Interestingly, the results obtained demonstrated that sleep deprivation and stress doesn’t produces differences in corticosterone levels at three conditions, sleep, stress and sleep deprivation. However, an increase was observed in the group of animals that were only infected33. We shown that even though sleep deprivation can be categorized as a type of stress, the main component of this is sleep loss, and the two stimuli have a differential effect in two compartments of the immune system, namely spleen and mesenteric lymph nodes; also, the populations responded different.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Interestingly, the results obtained demonstrated that sleep deprivation and stress doesn’t produces differences in corticosterone levels at three conditions, sleep, stress and sleep deprivation. However, an increase was observed in the group of animals that were only infected33. We shown that even though sleep deprivation can be categorized as a type of stress, the main component of this is sleep loss, and the two stimuli have a differential effect in two compartments of the immune system, namely spleen and mesenteric lymph nodes; also, the populations responded different.…”
Section: Discussionmentioning
confidence: 79%
“…We find tha natural killer cells (NK+) are most responsive to sleep deprivation, and the stress response is more heterogeneous. However, in that study we did not evaluate other mechanisms of host defence33.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations